2021
DOI: 10.46328/ijemst.2163
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Manipulative Games to Improve Fundamental Motor Skills in Elementary School Students

Abstract: This study aims to improve fundamental motor skill skills by using manipulative games. The method used in this study was experimental using a one-group pretest-posttest design. The research was conducted by applying manipulative games in physical education learning. To measure and find out the results of the data obtained by researchers using the statistical package for the social sciences (SPSS) software. The sample in this study was elementary school students with a total of 30 students. Random sampling with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…In other words, the potential for manipulative basic movement skills of a child is very important to be developed more optimally if the child wants to have maximum motor development. As stated by Dewi and Verawati (2021), the research results showed an increase in basic motor skills of elementary school students through manipulative games.…”
Section: Introductionmentioning
confidence: 62%
“…In other words, the potential for manipulative basic movement skills of a child is very important to be developed more optimally if the child wants to have maximum motor development. As stated by Dewi and Verawati (2021), the research results showed an increase in basic motor skills of elementary school students through manipulative games.…”
Section: Introductionmentioning
confidence: 62%
“…In addition, game-based learning presents an ongoing challenge because it is necessary to find and design diverse game activities and adapt their learning to the needs and interests of students (Avdiu 2019).Furthermore, the study results revealed that quiz games were suitable for elementary school students since school age is a period where students have to play more than stay silent (Gustiana 2011). By using games, it can make students' hearts happy; not only that but games are also an important part of human life, especially for elementary school students, because games have become an inherent feature of students; thus, games are the main activity carried out by students (Dewi and Verawati 2022). The development of this quiz game was in accordance with the characteristics of elementary school students who still like to play so that the next stage could be carried out to improve the reading skills of Javanese scripts.…”
Section: Discussionmentioning
confidence: 99%
“…The second finding in our study showed that traditional sport have a positive impact on improving students' social attitudes. According to previous study reports, traditional sport not only have significant capability to develop students' movement skills but can also be used to develop social skills, because it has the values of discipline, responsibility, exercises, honesty, tenacity, patience (Dewi & Verawati, 2021). Moreover, this exercise can train teamwork and build a friendly, caring, and patient character.…”
Section: Discussionmentioning
confidence: 99%